Harnessing ICT for English Language Learning in Indonesia: Challenges and Opportunities - Nugraha, Aditya P.; Duriat, Fajar; Rusdayanti, Rusdayanti (NOBEL: Journal of Literature and Language Teaching, 2024)
During the COVID-19 pandemic, online learning became mandatory, leading to the use of various apps, tools, and teaching methods to ensure the learning process continued. This systematic review examines the impact of implementing ICT in English Language Learning, specifically for students in school settings during the pandemic. The review included 87 studies based on exclusion/inclusion criteria. The findings from this literature review revealed that ICT practices in English language teaching resulted in positive outcomes, with 91% of the studies reporting improved language skills. Digital tools, multimedia, and visual aids enhanced student motivation, comprehension, and engagement, although some challenges were encountered. Integrating ICT tools like Zoom, Google Meet, Microsoft Teams, and Google Classroom became essential in education during and post-pandemic. Synchronous and asynchronous learning and communication tools like WhatsApp and Telegram proved effective for English language learning. Visual-based tools and multimedia content, including YouTube and animations, significantly improved language skills and created an engaging learning environment. However, challenges such as digital access inequity, technical competencies, lack of personal connection, pedagogical adaptation, and health-related concerns need to be addressed for effective and inclusive future implementation in English Language Learning.